Augmented Mechanical Forces of the Surface-Modified Nanoporous Acupuncture Needles Elicit Enhanced Analgesic Effects - Bae, Sun-Jeong; Lim, Junsik; Lee, Sangmin; Choi, Hansaem; Jang, Jae-Hwan; Kim, Yu-Kang; Oh, Ju-Young; Park, Jeong Hun; Jung, Hyuk-Sang; Chae, Younbyung; In, Su-Il; Park, Hi-Joon (Frontiers in Neuroscience, 2019)
Over the past several decades, clinical studies have shown significant analgesic effects of acupuncture. The efficacy of acupuncture treatment has improved with the recent development of nanoporous needles (PN), which are produced by modifying the needle surface using nanotechnology. Herein, we showed that PN at acupoint ST36 produces prolonged analgesic effects in an inflammatory pain model; the analgesic effects of PN acupuncture were sustained over 2 h, while those using a conventional needle (CN) lasted only 30 min. In addition, the PN showed greater therapeutic effects than CN after 10 acupuncture treatments once per day for 10 days. We explored how the porous surface of the PN contributes to changes in local tissue, which may in turn result in enhanced analgesic effects. We showed that the PN has greater rotational torque and pulling force than the CN, particularly at acupoints ST36 and LI11, situated on thick muscle layers. Additionally, in ex vivo experiments, the PN showed greater winding of subcutaneous connective tissues and muscle layers. Our results suggest that local mechanical forces are augmented by the PN and its nanoporous surface, contributing to the enhanced and prolonged analgesic effects of PN acupuncture.